Dealing with the Crisis - Stephanou, Constantinos (World Bank, Washington, DC, 2012)
The immediate financial sector policy responses to the financial crisis, including emergency liquidity support, expansion of financial safety nets, and interventions in financial institutions, have succeeded in stemming widespread panic. But the effort has generally been insufficient and ad hoc. Issues that remain include the resolution of problem assets, the restructuring of troubled, systemically important financial institutions, and the development of credible exit strategies. Only a handful of countries have attempted to tackle these issues head-on. As past experience has shown, that may well have negative repercussions for the duration and strength of a subsequent recovery.